Stability Analysis of Magnetic Gear with Thin Metal Sheet - Jing Libing Chen Junlin (Jixie chuandong)
In the transmission process of coaxial magnetic gear, aiming at the problems of large torque ripple and high magnetic density in air-gap, a magnetic gear with thin metal sheet is studied. The structure fixates a layer of conductive and non-magnetic metal material respectively on the internal and external permanent magnets of the rotor in the magnetic gear. A magnetic gear model with 4 opposite poles for inner rotor and 21 opposite poles for outer rotor is established via finite element method. The internal and external air-gap magnetic field and torque of the magnetic gear are calculated. Meanwhile, high magnetic density and torque ripple are analyzed. The results demonstrate that the magnetic gear with metal sheet can not only reduce the high-order harmonic components of magnetic density but also reduce the torque ripple. A reference for the improvement of the stability in the magnetic gear transmission is provided.